Iron Status in Newly Diagnosed β-Thalassemia Major: High Rate of Iron Status due to Erythropoiesis Drive. (17th April 2021) - Susanah, Susi; Rakhmilla, Lulu Eva; Ghozali, Mohammad; Trisaputra, Jessica Oktavianus; Moestopo, Octawyana; Sribudiani, Yunia; Idjradinata, Ponpon S.; Maskoen, Ani Melani
Abstract : Background . Iron overload in severe β -thalassemia is a serious complication that occurs during the course of the disease. Information about the iron status during initial illness with β -thalassemia major seemed to be limited. This study is aimed at analyzing iron status, serum hepcidin, and growth differentiation factor 15 (GDF15) levels in newly diagnosed β -thalassemia major. Methods . A case-control study was performed at Dr. Hasan Sadikin General Hospital, which included 41 children with newly diagnosed β -thalassemia major. Age- and sex-matched controls were enrolled. The subjects had no blood transfusion, had normal liver function, and had no sign of inflammation. The groups were compared in terms of the levels of hemoglobin (Hb), serum ferritin (SF), transferrin saturation (TS), serum hepcidin, and GDF15 as iron homeostasis parameters. Results . Of the 41 newly diagnosed β -thalassemia major patients, those who were less than 24 months old had significantly lower median Hb levels than controls (5.0 vs. 11.7 g/dL, P < 0.001 ). The median SF and TS levels were significantly higher than those in controls (315.0 vs. 29.0 ng/mL, P < 0.001 ; 70.6 vs. 16.5%, P < 0.001 ), and median hepcidin was at the normal limit, but the value was higher in patients (251.0 vs. 123.1 ng/mL, P < 0.001 ). The median GDF15 level was significantly higher in patients (2, 095.3 vs. 342.4 pg/mL, P < 0.001 ). There was a positive correlation between SF-TS, SF-hepcidin, TS-hepcidin, SF-GDF15, TS-GDF15, and hepcidin-GDF15 (P < 0.001 ). Conclusion . In newly diagnosed β -thalassemia major, an increase in iron status occurred. This may be caused by increased iron absorption due to massive erythropoietic activity, characterized by an increase in GDF15 levels, which does not cause hepcidin suppression. The iron homeostasis response seems to be physiologically indicated by a tendency to increase hepcidin levels.